Key determinants of blood sugar control in reproductive-age women with type 2 diabetes in Indonesia - Yonifa, Fidya Puspitasari; Subrata, Sumarno Adi; Kamal, Sodiq (Innovation in Health for Society, 2024)
Type 2 diabetes often affects women due to a combination of physical and psychological factors. For women of reproductive age, complications include prenatal morbidity and mortality, increased rates of cesarean deliveries, and chronic hypertension. When left untreated, this will impact the patient's quality of life. This study aims to identify the risk factors influencing blood sugar control among women of reproductive age with type 2 diabetes. A correlational study design was employed, with a sample of 43 respondents selected using total sampling techniques. Multiple linear regression was used for statistical analysis. The study identified significant associations between blood sugar control and risk factors such as body mass index, physical activity, food intake, and employment (p < 0.05). Further research is necessary to explore these risk factors in greater depth and to develop targeted nursing interventions. Keywords: Diabetes care; women health; community nursing; risk factors; preventive strategies